Sieci współrządzenia w procesach rewitalizacji = Co-governance networks in revitalization processes - Mielczarek-Żejmo, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Given how important participation of public sector and non-governmental actors is in revitalization, the article aims to determine the possibility of shaping relations among such stakeholders in conditions of representative democracy. The key questions concern the ways of involving various actors in democratic systems in the revitalization process, the nature of relations among revitalization participants in conditions of representative democracy, in particular between local governments and other participants, as well as other conditions (factors and barriers) for the effectiveness of cooperation network in revitalization.
Keywords: rewitalizacja; instytucje demokracji przedstawicielskiej; partycypacja; sieci współrządzenia; revitalization; representative democracy; participations; governance networks